Determining the relationship between cagA+ Helicobacter Pylori infection and microalbuminuria in type2 diabetic rats - Mansoureh Ahrarifar; Majid BaseriSalehi (Fasa University of Medical Sciences, 2017)
Background & Objectives: Microalbuminuria is a metabolic disease, which is related to the development of diabetic nephropathy. There are several reports indicating high frequency of the occurrence of Helicobacter pylori infection in diabetic patients. It means that probably, there is a relationship between cagA positive Helicobacter pylori and microalbuminuria in diabetic patients. Hence, the present study was conducted to investigate the relationship between cagA positive Helicobacter pylori infection and microalbuminuria in the patients with type 2 diabetes. Material & Methods: Totally, 76 blood and urine samples were collected from patients with type 2 diabetes. The blood samples were used to assess Glycoside Hemoglobin, Fasting Blood Sugar, two-hour postprandial Glucose, Anti-HpIgG and Anti-HpIgM. Molecular method was carried out for identification and helicobacter pylori positive samples were tested for the detection of cagA gene. Finally, Chi-Square test and Fisher technique were applied to analyze the data. Results: The results obtained from this study indicated that Helicobacter pylori was isolated from 28 patients (36.84%) from which, 21 patients (75%) were afflicted with microalbuminuria and 8 samples (25%) were cagA genes positive. The results indicated that there was no statistically significant difference between cagA gene of Helicobacter pylori and microalbuminuria in patients with type 2 diabetes. Conclusion: the findings showed that there was no significant correlation between cagA gene positive Helicobacter pylori infection, and microalbuminuria in the patients with type 2 diabetes.